Uy atrofiga ekilgan gullarning biologik xususiyatlari va ekologik talablari bo‘yicha tahlil (rosa spp., petunia hybrida, salvia splendens, callistephus chinensis, begonia semperflorns) - Kutlymuratova, Gulparshyn Atamuratovna; Kuandikova, Asem Ordabayevna; Utemuratova, Sarbinaz Umirzakovna (SCIENCE and SOCIETY, 2026)
The study was conducted in the spring of 2025 to investigate the growth, flowering, and ecological adaptability of rose (Rosa spp.), petunia (Petunia hybrida), and scarlet sage (Salvia splendens) planted in the home garden. The results showed that rose and scarlet sage grow rapidly, while petunia provides aesthetic appeal. Temperature, soil moisture, light, and watering significantly affect plant growth and flowering.
Keywords: home garden; rose (Rosa spp.); petunia (Petunia hybrida); scarlet sage (Salvia splendens); growth; flowering